Podophyllum hexandrum Offers Radioprotection by Modulating Free Radical Flux: Role of Aryl-Tetralin Lignans. Issue 4 (2006) - Chawla, Raman; Arora, Rajesh; Singh, Shikha; Sagar, R. K.; Sharma, Rakesh Kumar; Kumar, R.; Sharma, A.; Tripathi, R. P.; Puri, C.; Khan, H. A.; Shawl, A. S.; Sultan, P.; et al.
Abstract : We have evaluated the effect of variation in aryl-tetralin lignans on the radioprotective properties of Podophyllum hexandrum . Two fractionated fractions of P. hexandrum [methanolic (S1) and chloroform fractions (S2)], with varying aryl-tetralin lignan content were utilized for the present study. The peroxyl ion scavenging potentials of S1 and S2 were found to be comparable [i.e. 45.88% (S1) and 41% (S2)] after a 48 h interval in a time-dependent study, whereas in a 2 h study, S2 exhibited significant ( P < 0.05) antioxidant activity in different metal ion + flux states. In the aqueous phase, S2 exhibited non-site-specific reactive oxygen species scavenging activity, i.e. 73.12% inhibition at 500 μg ml−1. S1 exhibited 58.40 ± 0.8% inhibition (at 0.025 μg ml−1) of the formation of reactive nitrite radicals, comparable to S2 (52.45 ± 0.825%), and also showed 45.01% site-specific activity (1000 μg ml−1), along with significant ( P < 0.05) electron donation potential (50–2000 μg ml−1) compared to S2. Such activities of S1 could be attributed to the significantly ( P < 0.05) higher levels of podophyllotoxin β- d -glucopyranoside (16.5 times) and demethyl podophyllotoxin glucoside (2.9 times) compared with S2. Together, these findings clearly prove that aryl-tetralin lignan content influences the radiation protective potential of the Podophyllum fractions to a great extent.